Sexually Dimorphic Regulation of EET Synthesis and Metabolism: Roles of Estrogen - Huang, An; Sun, Dong (Frontiers in Pharmacology, 2018)
Epoxyeicosatrienoic acids (EETs) are metabolites of arachidonic acid via cytochrome P450 (CYP)/epoxygenase and are hydrolyzed by soluble epoxide hydrolase (sEH). Circulating and tissue levels of EETs are controlled by CYP (EET synthesis) and sEH (EET degradation). Therefore, both increases in CYP activity and decreases in sEH expression potentiate EET bioavailability, responses that prevail in the female sex as a function of estrogen. This mini review, based on subtitles listed, briefly summarizes studies focusing specifically on (1) female-specific potentiation of CYP/epoxygenase activity to compensate for the endothelial dysfunction; and (2) estrogen-dependent downregulation of sEH expression, which yields divergent actions in both systemic and pulmonary circulation, respectively. Estrogen-Potentiating EET Synthesis in Response to Endothelial Dysfunction: This section summarizes the current understanding regarding the roles of estrogen in facilitating EET synthesis in response to endothelial dysfunction. In this regard, estrogen recruitment of EET-driven signaling serves as a back-up mechanism, which compensates for NO deficiency to preserve endothelium-dependent vasodilator responses and maintain normal blood pressure. Estrogen-Dependent Downregulation of Ephx2/sEH Expression: This section focuses on molecular mechanisms responsible for the female-specific downregulation of sEH expression. Roles of EETs in Systemic Circulation, as a Function of Estrogen-Dependent Downregulation of sEH: This section summarizes studies conducted on animals that are either deficient in the Ephx2 gene (sEH-KO) or have been treated with sEH inhibitors (sEHIs), and exhibit EET-mediated cardiovascular protections in the cerebral, coronary, skeletal, and splanchnic circulations. In particular, the estrogen-inherent silencing of the Ephx2 gene duplicates the action of sEH deficiency, yielding comparable adaptations in attenuated myogenic vasoconstriction, enhanced shear stress-induced vasodilation, and improved cardiac contractility among female WT mice, male sEH-KO and sEHI-treated mice. Roles of Estrogen-Driven EET Production in Pulmonary Circulation: This section reviews epidemiological and clinical studies that provide the correlation between the polymorphism, or mutation of gene(s) involving estrogen metabolism and female predisposition to pulmonary hypertension, and specifically addresses an intrinsic causation between the estrogen-dependent downregulation of Ephx2 gene/sEH expression and female-susceptibility of being pulmonary hypertensive, a topic that has never been explored before. Additionally, the issue of the “estrogen paradox” in the incidence and prognosis of pulmonary hypertension is discussed.